The Age Factor Revisited: Timing in Acquisition Interacts With Age of Onset in Bilingual Acquisition - Schulz, Petra; Grimm, Angela (Frontiers in Psychology, 2019)
In this paper we investigate whether timing in monolingual acquisition interacts with age of onset and input effects in child bilingualism. Six different morpho-syntactic and semantic phenomena acquired early, late or very late are considered, with their timing in L1 acquisition varying between age 3 (subject-verb agreement) and after age 6 (case marking). Data from simultaneous bilingual children (2L1) whose mean age of onset to German was three months are compared with data from early second language learners of German (eL2) whose mean age of onset to German was 35 months as well as with data from monolingual children. To explore change over time, children were tested twice at the ages of 4;4 years and 5;8 years. The main findings were that 2L1 children had an advantage over their eL2 peers in early acquired phenomena, which disappeared with time, whereas in late acquired phenomena 2L1 and eL2 children did not differ. Moreover, 2L1 children performed like monolingual children in early acquired phenomena but had a disadvantage in the late acquired phenomena with the amount of delay decreasing with time. We conclude that age of onset effects are modulated by effects of timing in monolingual acquisition. Contrary to expectation, input in terms of language dominance, measured as the dominant language used at home, did not affect simultaneous bilingual children’s performance in any of the phenomena. We discuss the implications of our findings for the hypothesis that acquisition of late phenomena is determined by input alone and suggest an alternative concept: the learner’s internal need for time to master a phenomenon, which is determined by its complexity and cross-linguistic robustness.